2010
DOI: 10.1037/a0021526
|View full text |Cite
|
Sign up to set email alerts
|

Intelligence and Substance Use

Abstract: Why do some individuals choose to drink alcohol, smoke cigarettes, and use illegal drugs while others do not? The origin of individual preferences and values is one of the remaining theoretical questions in social and behavioral sciences. The Savanna-IQ Interaction Hypothesis suggests that more intelligent individuals may be more likely to acquire and espouse evolutionarily novel values than less intelligent individuals. Consumption of alcohol, tobacco, and drugs is evolutionarily novel, so the Savanna-IQ Inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

8
34
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 44 publications
(43 citation statements)
references
References 50 publications
8
34
1
Order By: Relevance
“…Consequently, in the absence of a real goal to pursue, wireheading is as valid an activity as anything else. It has been shown that smarter people are more likely to experiment with drugs (Kanazawa & Hellberg, 2010). This directly supports our explanation as a more intelligent agent in the absence of a set goal will tend to do more exploration (Savanna-IQ Interaction Hypothesis) (Kanazawa & Hellberg, 2010).…”
Section: Journal Of Experimental and Theoretical Artificialsupporting
confidence: 78%
See 1 more Smart Citation
“…Consequently, in the absence of a real goal to pursue, wireheading is as valid an activity as anything else. It has been shown that smarter people are more likely to experiment with drugs (Kanazawa & Hellberg, 2010). This directly supports our explanation as a more intelligent agent in the absence of a set goal will tend to do more exploration (Savanna-IQ Interaction Hypothesis) (Kanazawa & Hellberg, 2010).…”
Section: Journal Of Experimental and Theoretical Artificialsupporting
confidence: 78%
“…It has been shown that smarter people are more likely to experiment with drugs (Kanazawa & Hellberg, 2010). This directly supports our explanation as a more intelligent agent in the absence of a set goal will tend to do more exploration (Savanna-IQ Interaction Hypothesis) (Kanazawa & Hellberg, 2010). As people go through their lives exploring, sometimes they stumble upon goals which seem to be particularly meaningful to them, such as taking care of a child (to which we have an evolutionary bias), which leads to a decrease in wireheading (drug abuse).…”
Section: Journal Of Experimental and Theoretical Artificialmentioning
confidence: 99%
“…Fifth, more intelligent children grow up to consume more alcohol more frequently, smoke more tobacco (but only in the US) and use more illegal drugs (Kanazawa & Hellberg, 2010). This is possibly because the human consumption of such psychoactive substances is evolutionarily novel, all originating less than 10,000 years ago.…”
Section: Introductionmentioning
confidence: 99%
“…It also explains the 'exception that proves the rule', why more intelligent individuals are more likely to consume illegal drugs (Kanazawa & Hellberg, 2010). Unlike most interpersonal and property crimes, the consumption of such substances is evolutionarily novel.…”
Section: Introductionmentioning
confidence: 99%
“…In longitudinal studies, higher childhood IQ has been positively associated with alcohol use and higher consumption levels in early and later adulthood (Johnson et al, 2008; Kanazawa & Hellberg, 2010). For example, in a U.S. national sample of young adults assessed over a 5-year interval, higher verbal IQ predicted increased risk for subsequent drinking and decreased risk for problems among drinkers even after covarying for socioeconomic status (Windle & Blane, 1989).…”
mentioning
confidence: 99%